Analisis Ketahanan V-Belt Pada Perancangan Mesin Disc Mill (Mesin Penepung) - Nandang Hisbullah; Reza Setiawan; Rizal Hanifi; Deri Teguh S (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the efforts to increase the competitiveness of farmers in addition to improving the quality of their agricultural products must also be able to handle agricultural products into commodities that have high selling prices. In other words, they must master post-harvest handling technology. One of these technologies is to turn these agricultural products into flour, including disc mill machines or storage machines. Because the V-Belt is a very vital engine component and has a major effect on the performance of a holding machine, in this case the planning of a V-Belt on a holding machine must be precise, and predictable for its long-term durability, so that farmers can prepare the allocation of funds for the purchase of V-Belt spare parts in the future One of the efforts to increase the competitiveness of farmers in addition to improving the quality of their agricultural products must also be able to handle agricultural products into commodities that have high selling prices. In other words, they must master post-harvest handling technology. One of these technologies is to turn these agricultural products into flour, including disc mill machines or storage machines. Because the V-Belt is a very vital engine component and has a major effect on the performance of a holding machine, in this case the planning of a V-Belt on a holding machine must be precise, and predictable for its long-term durability, so that farmers can prepare the allocation of funds for the purchase of V-Belt spare parts in the future